Architecting the Metaverse: A Paradigm Shift for Co-design in Architecture - Eloy, S.; Raposo, M.; Pereira da Silva, N. (Digital Innovations in Architecture, Engineering and Construction, 2025)
Although already used since the last decade of the 20th century, the concept of metaverse has gained relevance in the last decade due to the advance-ments of virtual reality, the gaming industry and the uptake of big IT compa-nies. Metaverse for architecture design has been increasingly mentioned and used in practice, education, and research. Metaverse and the Extended Reality (XR) technologies that compose it and the multiuser possibilities enable immersive 3D experiences and interactions that engage multiple senses, creating a strong sense of presence in virtual environments. This heightened presence facilitates a deep understanding of spatial surroundings, allowing designers and laypeople to explore the built environment thoroughly. This paper explores the metaverse’s potential as a collaborative design tool in architecture, emphasising its real-time interactive capabilities and support for participatory design. We examine leading metaverse platforms, focusing on key features crucial for architectural design, namely, 3D modelling options, customisation tools, interaction features, and co-presence. Furthermore, we present three case studies using metaverse, illustrating its utility across different architectural research scenarios. These cases involve co-design, user studies evaluating the built environment quality, and simulations of construction processes.